Gejolak dan Dinamika Advokasi Politik Amerika Serikat - Yusuf, Revi Rizky; Lubis, Flori Mardiani (Peneliti.net, 2025)
ABSTRACT This study aims to examine the differentiation of US political advocacy based on differences in leadership styles and campaign periods for presidential candidates. In order to facilitate the readers, writer are using the Qualitative Descriptive method to explain all the main cause, differences and struggles both Internal nor External for the United States. Writer also made a sub-chapter to define the Idiosyncratic of the leaders, and to clarify the topics studied and by dividing the sub-chapters it to made it easier to understand Political advocacy and Soft-Power Diplomacy are like two things that has a strong correlations, in terms of applying both of these things we must be able to gain the trust of the people to succeed. In this research, we are going to define the differences of Political Advocacy and Soft-Power Diplomacy efforts of the United States President and politician based on the campaign. The turmoil and dynamics that happened are an example of a fail attempt of the main goal, and the difference main goal of every leader are as we called as Idiosyncratic. Which in the end, every leader must faced the struggles on leading a country, whether both of internal nor external struggles. The results of this research are that every leaders not always had a resemblences to each others, but the Idiosyncratic itself who define the leaders main goal for the United State.